Vol. 48 : Space Engineering IV Russian Forum for Young Scientists with International Participation, April 12-14, 2016, Tomsk, Russia [proceedings] - Borikov V. N. Valery Nikolaevich; Dolgikh A. G. Antonina Gennadievna; Ivanova V. S. Veronika Sergeevna; Ignatovskaya A. A. Anastasiya Albertovna (Les Ulis, 2016)
Title screen